2019
DOI: 10.1136/bmjpo-2019-000566
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of perinatal post-mortem ultrasound (PMUS): a systematic review

Abstract: ObjectiveUltrasound is ubiquitous in live paediatric imaging; however, its usage in post-mortem setting is less established. This systematic review aims to evaluate the diagnostic accuracy of paediatric post-mortem ultrasound (PMUS).DesignMEDLINE, Embase and Cochrane Library databases were queried for studies published between 1998 and 2018 assessing PMUS diagnostic accuracy rates in children<18 years old, using autopsy as reference standard. Risk of bias was assessed using Quality Assessment of Diagnostic Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…To date, seven systematic reviews have attempted to address the evidence. [25][26][27][28][29][30][31] However, it is clear that there are major limitations to the search methodologies in these reviews, potentially introducing bias, which means that the results cannot be interpreted with confidence. With the exception of the review by Wojcieszek et al, these reviews all focus on imaging techniques and do not consider other viable non-invasive or minimally invasive techniques.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To date, seven systematic reviews have attempted to address the evidence. [25][26][27][28][29][30][31] However, it is clear that there are major limitations to the search methodologies in these reviews, potentially introducing bias, which means that the results cannot be interpreted with confidence. With the exception of the review by Wojcieszek et al, these reviews all focus on imaging techniques and do not consider other viable non-invasive or minimally invasive techniques.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…With the exception of the review by Wojcieszek et al, these reviews all focus on imaging techniques and do not consider other viable non-invasive or minimally invasive techniques. [25][26][27][28][29][30][31] Similarly, the population groups are highly variable. Some consider a whole of life population, while others consider few very distinct perinatal populations.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…73 It may also be better understood by parents when consenting for post-mortem imaging having already undergone ante-natal ultrasound scanning and is also unaffected by tissue fixation. 61,72,[74][75][76][77] PMUS also has the advantage of being able to direct needle biopsies for tissue sampling. 47,73,[78][79][80][81] However, PMUS is operatordependent, requiring specialist training to develop the skills and experience to accurately identify possible causes of pregnancy loss in these smaller fetuses.…”
Section: Post-mortem Ultrasoundmentioning
confidence: 99%
“…61 Although relatively high sensitivities and specificities have been reported from multiple studies (ranging from 73% to 97%, similar to 1.5T PMMR), most studies have found lower diagnostic rates and higher yield of non-diagnostic imaging in fetuses below 20 weeks gestation. 51,61,72,75,76…”
Section: Post-mortem Ultrasoundmentioning
confidence: 99%
“…When the imaging is of diagnostic quality, ultrasound has been reported to have a similar accuracy to both 1.5 T [ 25 ] and 3 T MRI [ 26 ], with an estimated overall sensitivity of 73% and specificity 97% (based on a systematic review of 455 perinatal losses)[ 27 ]. The highest sensitivity rates were found for brain imaging (84%) and lowest for cardiothoracic abnormalities (51%).…”
Section: How Accurate Are the Different Post-mortem Imaging Modalities?mentioning
confidence: 99%